2010
DOI: 10.1111/j.1462-5822.2010.01433.x
|View full text |Cite
|
Sign up to set email alerts
|

Secreted cysteine proteases of the carcinogenic liver fluke, Opisthorchis viverrini: regulation of cathepsin F activation by autocatalysis and trans-processing by cathepsin B

Abstract: SummaryOpisthorchis viverrini is an important helminth pathogen of humans that is endemic in Thailand and Laos. Adult flukes reside within host bile ducts and feed on epithelial tissue and blood cells. Chronic opisthorchiasis is associated with severe hepatobiliary diseases such as cholangiocarcinoma. Here we report that adult O. viverrini secrete two major cysteine proteases: cathepsin F (Ov-CF-1) and cathepsin B1 (Ov-CB-1). Ov-CF-1 is secreted as an inactive zymogen that autocatalytically processes and activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 55 publications
2
28
0
Order By: Relevance
“…Affinity purified r Ov -CB-1 migrated in SDS-PAGE as a single species at ~44 kDa, which is the active form of the enzyme [14] (Figure 1, lane 3). Immunoblot analysis showed that r Ov -CB-1 was recognized by O. viverrini positive human sera, revealing a major band of recognition at 44 kDa, whereas control, non- O. viverrini infected sera showed no reactivity (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Affinity purified r Ov -CB-1 migrated in SDS-PAGE as a single species at ~44 kDa, which is the active form of the enzyme [14] (Figure 1, lane 3). Immunoblot analysis showed that r Ov -CB-1 was recognized by O. viverrini positive human sera, revealing a major band of recognition at 44 kDa, whereas control, non- O. viverrini infected sera showed no reactivity (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Recombinant O. viverrini cathepsin B1 (r Ov -CB-1) (GenBank accession number ACT99885) was produced in Pichia pastoris as described [14]. Recombinant proteins were purified using Ni-NTA affinity columns (Novagen) and dialyzed against phosphate buffered saline (PBS) at pH 7.2–7.4 through dialysis membrane (SnakeSkin TM Pleated Dialysis Tubing, Pierce) for 4 h at 4°C and stored at −20°C until used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several reports relating cathepsin F to the molecular mechanisms of host invasion by parasitic worms such as Clonorchis sinensis (156) , Teladorsagia circumcincta (157) , Opisthorchis viverrini (158) , and Manduca secta (159) . Indeed, in Asian flukes from the genera Clonorchis , Paragonimus , and Opsthorchis , cathepsin F-like peptidases are the predominantly expressed cysteine peptidases (140) .…”
Section: Cathepsin F-like Peptidasesmentioning
confidence: 99%
“…Thus, oligo/polypeptide fragments do not accumulate to the extent observed for hemoglobin digestion by helminth cathepsin L-type endopeptidases (65)(66)(67). With regard to hemoglobinolytic capability, SmCB1 resembles cathepsins B from the Southeast Asian liver fluke Opisthorchis viverrini and the hookworm Ancylostoma caninum (66,68) but differs from cathepsins B of the avian fluke Trichobilharzia regenti and the hookworm Necator americanus that cannot initiate hemoglobinolysis (69,70). We conclude that SmCB1 operates as an effective proteolytic machine to degrade the major protein in the parasite's blood meal.…”
Section: Smcb1 An Efficient Endo-and Exopeptidolytic Machine-mentioning
confidence: 99%